A clinico-mycological and histopathological study of recurrent dermatophytosis - Y Urmila; K V T. Gopal; Narayana Rao Turpati; Sudhir Babu Karri; P V K. Raju (Wolters Kluwer Medknow Publications, 2023)
Background: A few recent studies have shown fungal elements within the hair follicle epithelium, which may act as a reservoir and responsible for recurrent dermatophytosis. Objectives: To assess the clinical patterns, mycological profile, and histopathology of recurrent dermatophytosis and to determine the prevalence of fungal hyphae in the hair follicle epithelium and other appendages. Materials and Methods: One hundred and fifty clinically diagnosed cases of recurrent dermatophytic infection were included. Skin samples were taken for direct microscopy, fungal culture, and histopathological analysis. Haematoxylin and eosin and special staining with periodic acid Schiff (PAS) and Gomori's methenamine silver (GMS) were performed to detect the fungal hyphae in the skin and hair follicle epithelium. Results: The most common clinical pattern observed was tinea corporis et cruris in 64 patients (42.66%). On direct microscopy and fungal culture, positive results were obtained in 116 cases (77.33%) and 78 (52%) cases, respectively. Presence of fungal hyphae in the stratum corneum, hair follicle, and acrosyringium was seen in 107 patients (71.33%), 47 patients (31.33%), and five patients (3.33%), respectively. Out of the 52 cases with hair follicle and eccrine gland involvement, history of fixed drug combinations (FDC) cream use was present in 42 cases (80.76%) and absent in ten cases (19.24%) (P = 0.000062). Limitations: Skin samples were taken only from a single skin lesion. Higher incidence of follicular invasion may have been detected if multiple biopsy samples were taken. Conclusion: Hair follicle/eccrine sweat gland involvement was observed in nearly one-third of the patients, which may act as a reservoir and may be responsible for recurrence and chronicity. Histopathology should be considered as an important adjuvant tool in recurrent dermatophytosis to establish the extent of the infection, which guides the further management.